The Physicochemical Characterisation and Computational Studies of Tilapia Fish Scales as a Green Inhibitor for Steel Corrosion - Ntiyiso Faith Nyambi; Kasturie Premlall; Krishna Kuben Govender (Engineering Proceedings)
The effect of increased corrosion in re-enforcement structures has led to the need to identify and develop more inexpensive, non-toxic, eco-friendly and readily available inhibitors from natural resources. Extensive research and development have led to the discovery of new classes of green corrosion inhibitors. In this work, Tilapia fish scales (FSs) were used as a green corrosion inhibitor as they are abundant in both organic components, such as collagen (C12H19N3O5), and inorganic components, such as hydroxyapatite (Ca10(PO4)6(OH)2). The FSs were subjected to a maceration process to extract all the inorganic and organic compounds. The FS extract was then characterised using an X-ray diffractometer (XRD), a scanning electron microscope (SEM) and Fourier transform infra-red (FTIR). Quantum computational studies were conducted in order to determine parameters such as the energy of the highest occupied molecular orbital (EHOMO) and the energy of the lowest occupied molecular orbital (ELUMO). The Gaussian 09 program density functional theory at the 6-311++(d,p) basis set was used to investigate the interaction between the organic and inorganic molecules, therefore examining both interaction energies. The XRD results confirmed that a large amount of hydroxyapatite was present in the extract, with a high diffractive peak at 32θ and small amounts of collagen picked up between 13θ and 25θ. SEM results showed the percentage weight of atoms, such as carbon (19.8%), calcium (27%), oxygen (41.3%) and phosphate (11.9%), which were found to be present in both the organic and inorganic part of the FS sample. FTIR results confirmed the presence of hydroxyl (3200–3500 cm−1), carbonate (1620–1700 cm−1) and phosphate groups (1200–800 cm−1). The computation studies showed that hydroxyapatite was the most reactive molecule, as it had the highest EHOMO of −0.2076 eV compared with that of collagen at −0.2470 eV. The interaction energy of the FS molecule was −615 kJ/mol.